2012
DOI: 10.1186/1471-2458-12-216
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in alcohol-related non-consensual sex; cross-sectional analysis of a student population

Abstract: BackgroundSexual offences are a global public health concern. Recent changes in the law in England and Wales have dramatically altered the legal landscape of sexual offences, but sexual assaults where the victim is voluntarily intoxicated by alcohol continue to have low conviction rates. Worldwide, students are high consumers of alcohol. This research aimed to compare male and female students in relation to their knowledge and attitudes about alcohol and sexual activity and to identify factors associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
27
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 50 publications
8
27
0
2
Order By: Relevance
“…Moral responsibility, however, still appeared to be something that could be forfeited when parties were equivalently intoxicated, but not when there was a disparity in that intoxication. These findings support the research that has identified that third parties perceive it unfair to hold a defendant criminally liable for rape if each individual is equally intoxicated (Finch and Munro, 2005;Gunby et al, 2012), yet are more inclined to label sex as rape when a complainant is drinking independently (Norris and Cubbins, 1992), or the defendant is less intoxicated (Finch and Munro, 2005). Whilst Finch and Munro (2005) argue that a less drunk or sober defendant is perceived to be in a position whereby he is able to ensure the complainant has the capacity to consent, the current study indicates that an intoxicated defendant is perceived to be in a disadvantageous position whereby he is unable to clearly gauge the complainant's level of intoxication, and therefore her capacity.…”
Section: Impact Of Alcohol On Inhibitionssupporting
confidence: 86%
See 1 more Smart Citation
“…Moral responsibility, however, still appeared to be something that could be forfeited when parties were equivalently intoxicated, but not when there was a disparity in that intoxication. These findings support the research that has identified that third parties perceive it unfair to hold a defendant criminally liable for rape if each individual is equally intoxicated (Finch and Munro, 2005;Gunby et al, 2012), yet are more inclined to label sex as rape when a complainant is drinking independently (Norris and Cubbins, 1992), or the defendant is less intoxicated (Finch and Munro, 2005). Whilst Finch and Munro (2005) argue that a less drunk or sober defendant is perceived to be in a position whereby he is able to ensure the complainant has the capacity to consent, the current study indicates that an intoxicated defendant is perceived to be in a disadvantageous position whereby he is unable to clearly gauge the complainant's level of intoxication, and therefore her capacity.…”
Section: Impact Of Alcohol On Inhibitionssupporting
confidence: 86%
“…Whilst certain participants argued that having drank alcohol prior to a rape is likely to decrease a complainant's likelihood of reporting the assault, due to fears around being perceived non-credible, the majority of participants argued that people are more likely to use alcohol 'as their excuse' (FG1, F5) for engaging in uninhibited behaviours. These findings support larger scale quantitative data which indicates that 81.1% of students (N ¼ 869) aged 18 to 24 years agreed that being drunk when having sex increases the likelihood of a false rape allegation being made (Gunby et al, 2012).…”
Section: Impact Of Alcohol On Inhibitionssupporting
confidence: 79%
“…Using such substances was a risk for problems of unsafe sexual practices that predispose them to sexually transmitted infections including unwanted pregnancy, HIV/IDS, and other consequences of unsafe sex. These problems were also the problems faced by university students in China and Sweden [22,23]. In Addis Ababa 22.0% use alcohol and 8.0% chew khat [10].…”
Section: Discussionmentioning
confidence: 99%
“…The campaign was designed by Liverpool City Council in conjunction with the advice of two of the article authors and encompassed four aims: firstly, to target men aged 18-24, both student and non-student NTE users, in recognition of men within this age range lacking legal understanding of consent (Abbey et al, 2004;Beres, 2007;Felts et al, 2012;Gunby et al, 2012a;Gunby et al, 2012b). Secondly, and related to this point, to clarify to the target audience that under English and Welsh law, engaging in sexual intercourse with someone unable to consent due to their alcohol intoxication, constitutes rape.…”
Section: Developing and Analysing The Impacts Of A Rape Prevention Camentioning
confidence: 99%
“…Those aged 18-24 (both students and non-students), have also been found to lack knowledge of the legal position on sexual consent: an issue made additionally complex when alcohol has been consumed (Beres, 2007;Gunby et al, 2012a;Gunby et al, 2012b). Running alongside, it has been recognised that rape prevention work must move beyond offering risk-reduction advice to women, to focus instead on the behaviours of men and the legal knowledge they should possess in order to reduce sexual offending (Stern Review, 2010).…”
Section: Introductionmentioning
confidence: 99%